Management of sap sucking insect populations on cotton plants by imidacloprid application and N P K fertilization - Aioub, A. A. A.; Raslan, S. A. A.; Gomaa, E. A.; Desuky, W. M.; Zaki, A. A. (2002)
Field experiments were conducted during the cotton growing seasons of 1998 and 1999 in Sharkia region, Egypt, to determine the effect of imidacloprid insecticide, as a seed dressing at the rate of 7 g. / kg. on germination, pest attacking cotton seedlings and their natural enemies as well as the effect of N, P and K fertilization on the levels of aphid and whitefly infestation to plants. The experimental results showed the following trends: , 1) Imidacloprid seemed to enhance and increase the emergence of cotton seeds. Cotton seedlings grown from imidacloprid - treated seeds were generally longer and more viable than those of the untreated control. 2) Treatments with imidacloprid protected cotton seedlings from sap sucking insects (e.g. white flies, aphids and thrips) for at least 10 weeks from the onset of seeds planting while resulted in poor effect on the jassid and mite invasion to cotton seedlings.
Includes references.
Summary in Arabic.
1
Keywords: Cotton -- Diseases and pests -- Control; Imidacloprid; Aphids -- Control